EFEKTIVITAS PENDAMPINGAN TERHADAP PERILAKU PERAWAT DALAM PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUANG HARDJA IA RS. BHAYANGKARA TK. I R. SAID SUKANTO - Feny Ditya Hanifah, (2022)
Nursing documentation is an authentic record carried out by a nurse. The quality of nursing documentation is assessed from several factors, including the absence of guidelines or SOPs regarding standardized documentation, lack of training attended by nurses, nurses' level of knowledge and attitudes, and lack of assistance or supervision carried out by the hospital regularly to patients. nurse. This writing aims to measure the effectiveness and determine changes in the behavior of nurses in documenting nursing care in the Hardja IA Hospital room. Bhayangkara Tk. I R. Said Sukanto. The method used is to conduct interviews, observations,,s andiscussionson together. The results of observations showed that there was a change in writing a complete nursing diagnosis with etiology (PE) problems from 33.3% to 100%, and the formulation of nursing goals was made to contain components of goals and outcome criteria from 50% to 83.3%, nursing action plans were prepared refers to the goals with clear and detailed sentences from 83.3% to 100%, the preparation of an action plan is ready and written describing the involvement of the client and the client's family from 50% to 100%, the evaluation of the nursing actions given refers to the goals and criteria for the results of 83, 3% to 100%, evaluation of the client's knowledge about his illness after conscious and independent health promotion from 16.7% to 100% and documentation activities at the stage of the nursing process must be written clearly, concisely and easefficientlyom 50% to 100%. The conclusion is that there is an influence between mentoring and nurse behavior in documenting nursing care Researchers suggest to hospital management can regularly evaluate and implement assistance or supervision activities. The authors hope that nurses can increase knowledge and compliance in the documentation of nursing care.